2022
DOI: 10.1136/bmjopen-2021-054902
|View full text |Cite
|
Sign up to set email alerts
|

Eid-al-Fitr festivity and Ramadan fasting attitude among individuals with diabetes from Saudi Arabia and Pakistan: a cross-sectional study

Abstract: ObjectivesThe present study aimed to assess the attitude of Saudi and Pakistani individuals with diabetes regarding Eid-al-Fitr festivities, exploring diabetes care during the month of Ramadan and these individuals’ dietary patterns on Eid day.DesignCross-sectional study.SettingJeddah (Saudi Arabia) and Karachi (Pakistan).ParticipantsOf the total 405 subjects, 204 individuals with diabetes from Saudi Arabia (SA) and 201 from Pakistan (Pak) were enrolled.Data collection and analysisThis survey-based study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A systematic review indicated that depression and anxiety in patients reduce their perception of QoL ( 27 ). QoL has a strong influence on the lives of individuals with diabetes and has a direct relationship with glycemic control ( 28 , 29 ). Therefore, we cannot manage an individual with DM without improving QoL.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review indicated that depression and anxiety in patients reduce their perception of QoL ( 27 ). QoL has a strong influence on the lives of individuals with diabetes and has a direct relationship with glycemic control ( 28 , 29 ). Therefore, we cannot manage an individual with DM without improving QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Their celebrations on different occasions were generally limited due to their DM problems. 30 As a result, their implicit knowledge and attitude towards diabetes, as well as prevention strategies, improved compared to individuals who did not have a DM member in their family. Another reason could be that they want to take diligent care of their loved ones; therefore, they educate themselves on diabetes.…”
Section: Discussionmentioning
confidence: 99%